Pengembangan Formula Enteral Tinggi Branched-Chain Amino Acid Berbasis Ikan Gabus, Putih Telur Bebek, dan Labu Kuning (GAPULA) - Gondosari, Misykat Huda Kesumo Rohmat Putri; Mustikaningrum, Fitriana; Kelimari, Rewinta Putri Denaru; Alfadila, Tsania Izza; Alam, Regita Shalsabillah Dhita; Swastikaningrum, Alifia Divana Ayu (Ghidza: Jurnal Gizi dan Kesehatan, 2025)
Liver cirrhosis is a disease of the liver organ that remains a concern in global health. Patients with cirrhosis and malnutrition can experience a higher incidence of complications compared to non-malnourished patients. To prevent the severity of malnutrition due to insufficient nutrient intake through oral food, the use of enteral nutrition high in Branched-Chain Amino Acids (BCAA) can be considered. The objective of this research is to determine the quality of a high BCAA enteral formula based on snakehead fish, duck egg whites, and pumpkin (GAPULA) in terms of nutritional content, osmolality, flow rate, viscosity, and formula acceptability. This research method employs an experimental design using two treatments with variations in the ratio of duck egg whites and snakehead fish in formula 1 at 1:1 and in formula 2 at 1:2. The results of this study indicate that there are differences in viscosity, osmolality, flow rate, and hedonic properties between formula 1 and formula 2. The best viscosity and flow rate were found in formula 2, which had a viscosity of 642.4 cP (P<0.05) and a flow rate of 0.7 cc/second. Meanwhile, the best osmolality was found in formula 1, which had an osmolality of 472 mOsmol/kg. The recommended formula is formula 2, which has a lower viscosity and an osmolality value that is not significantly different from formula 1.